Comparative studies on "body writing" in Calixthe Beyala and Ahlam Mosteghanemi - (:unkn) unknown (My University, 2015)
The goal of this thesis is the study of way tow African novelists describe the body ; Ahlam Mosteghanemi from Algéria and Calixthe Beyala from Cameroon. Our analisis traces the writings about the body to a symbolic structure where social discourses meet literary practices. The writings about the body, male or female, are studied from a perspective locked in the problematics of social and literary practices. More than a simple description, the body becomes an esthetic disguise through which the two novelists bypass censorship to tackle all their cultural taboos. Thus the sphere of the body combines discourses of subversion and reversal as well as negotiation and self censorship. What’s more, the body subject of literature bears in itself a tearing, a division and a suffering and seems to only understand and live its existence in pain and difficulty. This literal body that feels and suffers expresses a relationship to the world and to others and is part of a quest for self-affirmation.
Keywords: African Research